Out of the studio the photographic innovations of Charles and John Smeaton at home and abroad - Osborne, John 1951-; Smeaton, Peter 1951-2021 (McGill-Queen’s/Beaverbrook Canadian Foundation studies in art history, 2022)
"Photography, one of the most influential inventions of the nineteenth century, has been shaped by Canadian innovators. Among them are two Quebec men who have flown beneath the radar in studies of the history of photography: the Smeaton brothers. Out of the Studio documents the life, oeuvre, and achievement of Charles Smeaton and his younger brother, John. Launched by the opening of their "photographic gallery" in 1861, they developed a reputation in Quebec for images of contemporaneous people, places, and events taken in challenging outdoor settings. Smeaton pictures of the aftermath of the Great Fire of Quebec in 1866 helped bring an understanding of the disaster to an international audience; images featuring the gold mining industry were displayed at the Exposition universelle in Paris the following year. When Charles travelled to Europe in 1866, he accomplished a feat previously thought impossible, taking the first successful photographs in the Roman catacombs. John moved to Montreal in 1869, where he worked for newspapers and developed techniques for the direct transfer of photographs into print without the necessity of intermediary engravings. Out of the Studio is the first comprehensive biographical study detailing the innovation and imagination of the Smeaton brothers and their legacy of images across two continents."--